Napoleão Bonaparte e Portugal. Patriotismo, Revolução e Memória Política da Resistência - Ana Cristina Araújo (Carnets)
Portugal had its “Napoleonic moment”. Before French occupation, the Regent Prince D. João and other prominent figures of the Court received the high distinction of the Legion of Honor and, in 1808, during the absence of the royal family, a group of citizens demanded the grant of a Constitution from the Emperor and the adoption of the Civil Code (1804). The episodes surrounding the action of the ‘afrancesados’ and the mobilization of resistance – both the elites and the people – show that the aspiration for political change and the fight for independence express different forms of patriotism.